Genotype-environment interaction and stability analyses in advanced rice mutants for grain yield and straw quality - Abisola, Oladosu Yusuff (2018)
Genotypes evaluation in diverse environments is a prerequisite for selecting ideal genotype (genotype with high mean yield with a low degree of fluctuations). These evaluations are essential especially when the objective of the breeding programme were to release a new varieties with high adaptability and stability for grain yield and straw quality. The main objective of this study was to assess the performance of selected rice mutant genotypes and check varieties across different growing environments for adaptability and interaction on yield, yield components and straw quality. A set of 15 rice genotypes was tested over 2 planting seasons (main and off season) in 5 locations across Peninsular Malaysia. The genotypes included 6 advanced mutant lines, 6 mutant varieties from Vietnam and Bangladesh, and 3 local commercial varieties as checks. The experiment was carried out in a randomized complete block design with three replications across the environments. Data were collected on vegetative traits, yield and yield component traits and straw quality traits. Analysis of variance revealed a significant difference among the genotypes, locations, seasons and genotype x location x season interaction for all the characters studied except for 100-grain weight, panicle length, crude fibre, neutral detergent fibre, acid detergent fibre and acid detergent lignin. Moderate heritability and genetic advance were also recorded for all the traits except 100-grain weight, panicle length and panicles per hill. Grain yield per hectare showed highly significant and positive correlations with most of the traits under this study at both phenotypic and genotypic level. By contrast, unfilled grains per panicle and plant height had a negative significant association with yield per hectare. Filled grains per panicle exhibited the maximum positive direct effect on yield followed by grain weight per hill, while unfilled grain per panicle had negative direct effect. The maximum indirect effect on yield per hectare was recorded by the tillers per hill through the panicles per hill. The study revealed that tillers per hill and grain weight per hill could be used as selection criteria for improved grain yield. The test environments that measure the discriminative and representative ability of test location reveal that environment Sekinchan (SC) is the best environment, while Kota Sarang Semut (KS) and Seberang Perai (SP) can also be considered as favourable environment, whereas Serdang (SS) and Tanjung Karang (TK) were the poorest locations for selecting cultivars adapted to the whole region. Based on univariate (bᵢ,S²d, σi², Wi², YSᵢ) and multivariate (AMMI and GGE biplot) stability analysis parameters, rice genotypes were classified into three main groups. First group were genotypes having high stability along with high grain yield. These genotypes include ML4 and ML6 and are widely adapted to diverse environmental conditions. The second group is genotype that exhibited high yield per hectare but low stability, this genotype (ML9) is suitable for specific environments. The last group is genotypes with low yield per hectare but high stability which includes genotypes MR220, Binadhan4, and Binadhan7.